2021
DOI: 10.7150/jca.63244
|View full text |Cite
|
Sign up to set email alerts
|

High-performance Collective Biomarker from Liquid Biopsy for Diagnosis of Pancreatic Cancer Based on Mass Spectrometry and Machine Learning

Abstract: Background: Most pancreatic cancers are found at progressive stages when they cannot be surgically removed. Therefore, a highly accurate early detection method is urgently needed. Methods: This study analyzed serum from Japanese patients who suffered from pancreatic ductal adenocarcinoma (PDAC) and aimed to establish a PDAC-diagnostic system with metabolites in serum. Two groups of metabolites, primary metabolites (PM) and phospholipids (PL), were analyzed using liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
0
11
0
1
Order By: Relevance
“…A total of 24 metabolomics studies focused on identifying disease biomarkers from PDAC patients were compiled [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The techniques used in each study, source of sample, and number of significantly identified metabolites are detailed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 24 metabolomics studies focused on identifying disease biomarkers from PDAC patients were compiled [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The techniques used in each study, source of sample, and number of significantly identified metabolites are detailed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Further, the lack of a comprehensive evaluation of these clinical studies hinders the identification of study design parameters that may negatively impact the reproducibility of the outcomes. To address these issues, we present a detailed analysis of 24 clinical pancreatic ductal adenocarcinoma (PDAC) metabolomics studies [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Our meta-analysis revealed an extensive variation in these studies and highlighted a substantial inconsistency in outcomes, but also identified a subset of metabolites that were identified across multiple datasets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…и фосфолипиды, были проанализированы в работе Iwano T. (2021). В итоге в скрининговый алгоритм были включены 36 статистически значимых метаболитов (15 первичных метаболитов, включая орнитин, уридин, аспарагиновую кислоту, глутаминовую кислоту, ксантин, гипоксантин и др., и 28 фосфолипидов) в качестве коллективного биомаркера, что улучшило результаты на 97,4% [67].…”
Section: процедуры скринингаunclassified
“…Recent years have witnessed increased interest in liquid biopsy for cancer diagnosis due to its noninvasive nature. Metabolomic analysis of bodily fluids, i.e., serum or urine, has been a popular approach and has prompted more than 1000 studies on cancer-diagnostic biomarkers. A related concept is “chemical biopsy,” which appeared in the literature more than five decades ago .…”
Section: Introductionmentioning
confidence: 99%